Efficient degradation of toxic mixed dyes through peroxymonosulfate activation by copper/iron nanoparticles loaded on 3D carbon: Synthesis, characterizations, and mechanism. Issue 3 (June 2022) - Yang, Jiapeng; Huang, Rong; Wang, Luyao; Luo, Dan; Wang, Chongqing
Abstract: Exploitation of heterogeneous catalysts with high activity, stability and reusability gains increasing worldwide attention due to the tremendous demand for purification of dye wastewater. Copper/iron bimetallic catalysts have been proven to be powerful for persulfate activation to generate reactive radical species. Copper/iron nanoparticles loaded onto porous carbon (Cu/FeNPs@PC) was innovatively designed and used as catalyst for peroxymonosulfate (PMS) activation. Cu/FeNPs@PC manifests high catalytic activity for dye degradation over a wide pH range (4.0–10.0). Under conditions of 0.2 g/L catalyst, PMS 0.15 g/L and pH 4.8, nearly complete degradation (98.4%) of Rhodamine B occurs after 18 min. The rate constant is between 0.0946 and 0.1911 min −1 depending on initial solution pH. Mixed dyes can be efficiently degraded verified by UV–vis spectra and color variation of dye solution. Cu/FeNPs@PC has good stability, magnetism, and reusability for recycling. A synergistic effect of promoting Cu 2+ /Cu + and Fe 3+ /Fe 2+ cycle is probability ascribed to the enhanced catalytic activity. The mechanism of catalytic degradation of dyes involves radical species (SO4 - and OH) and non-radical pathways including 1 O2 and mediated electron transfer. This work provides insights into rational design of binary metal catalysts that apply to treatment of dye wastewater. Graphical Abstract: ga1 Highlights: Copper/iron nanoparticles loaded on 3D carbon was synthesized and used as catalyst. Cu/FeNPs@PC as catalyst shows good stability, magnetism, and reusability. Efficient degradation of mixed dyes is obtained in Cu/FeNPs@PC and PMS system. Mechanism involving radical and non-radical pathway is revealed for dye degradation.